Antimicrobial and anti-oxidant activities of quinoline alkaloids from Pseudomonas aeruginosa BCC76810. (September 2016) - Supong, Khomsan; Thawai, Chitti; Supothina, Sumalee; Auncharoen, Patchanee; Pittayakhajonwut, Pattama
Graphical abstract: Highlights: Twelve 4-hydroxyqunolines and three phenanzines were isolated from Pseudomonas aeruginosa BCC76810. The compounds were evaluated for antimicrobial and anti-oxidant activities. 4-Hydroxyquinoline derivatives exhibited strong antimalarial activity. Abstract: Twelve 4-hydroxyquinoline derivatives (1 –12 ) and three phenazine alkaloids (13–15 ) have been isolated from Pseudomonas aeruginosa BCC76810. All these compounds, except compounds6, 7, 9, and11, are known. The new quinolines are 2-(( Z )-undec-4′-enyl)-4-hydroxyquinoline (6 ), 2-(3′-(2′-hexylcyclopropyl)propyl)-4-hydroxyquinoline (7 ), 2- n- octyl-4-hydroxyquinoline N -oxide (9 ), and 2-(( Z )-undec-4′-enyl)-4-hydroxyquinoline N -oxide (11 ). Their structures were elucidated based on the spectroscopic information, such as 1D, 2D NMR, UV, and HRESIMS data. 4-Hydroxyquinolines (1 –6 ) and 4-hydroxyquinoline- N- oxides (8 –11 ) exhibited antimalarial activity against Plasmodium falciparum, K1 strain (IC50 0.25–2.07 μg/mL) with moderate to weak cytotoxicity against cancerous (KB, MCF-7, NCI-H187) and non-cancerous (Vero) cells. In addition, 4-hydroxyquinoline N -oxides also displayed anti- Bacillus cereus and antioxidant activities.